A transição do ensino fundamental I para o ensino fundamental II na vida de um aluno com deficiência - Guerreiro, Guacyara Labonia (2012)
The primary goal of this study is to analyze the inclusion process of students with disabilities from Elementary School to Middle School. With this purpose, it begins with a brief introduction of the legal and theoretical aspects that support and justify the inclusion process of students with disabilities in standard schools in the last few years. After that, through a qualitative approach, a case study was determined as the methodology, reinforcing the reflection on the issues at hand. Results have shown that there still are frailties related to the inclusion of students with disabilities in standard schools and that the current educational system can’t provide for every student. One possible conclusion of this case study is that all the knowledge acquired by the student during the early years of Elementary School is disregarded in Middle School. Moreover, this research suggests that the existent gap in the transition from one stage of the student’s education to the other creates a seeming “unpreparedness” to attend the last years of Middle School - hastily associated with their disability – disguising the school’s difficulty to rethink its work through an inclusive perspective. The conclusions reached highlight the pressing need for change in the current model, with the intention of reorganizing school practices, mainly the ones concerning the transition from Elementary School to Middle School.